Perlindungan Hukum bagi Bank Penyedia Fasilitas Kredit Pemilikan Rumah pada Bank Tabungan Negara Kantor Cabang Cibubur - Meiliza Putri Yanti; Esther Tarigan; Elianta Ginting (Perspektif Administrasi Publik dan hukum, 2025)
This research discusses legal protection for banks as providers of Home Ownership Credit (KPR) facilities at Bank Tabungan Negara (BTN) Cibubur Branch Office. The aim of this research is to analyze the implementation of legal protection for banks in the event of default by the debtor, especially when the Deed of Granting Mortgage Rights has not been attached to the collateral object due to administrative obstacles. One of the main obstacles is the validity period of the Power of Attorney to Encumber Mortgage Rights which has expired before the process of installing Mortgage Rights is completed. The main problems in this research include: (1) the procedure for granting mortgages at the BTN Cibubur Branch, (2) legal protection for banks if they fail to install Mortgage Rights, and (3) factors that cause delays in installing Mortgage Rights. This research uses an empirical juridical approach with qualitative methods, based on applicable laws and regulations. Data collection techniques include literature study, observation, and interviews. The research results show that BTN Cibubur Branch has carried out procedures according to operational standards and strengthened its legal protection through credit agreements and notarial deeds. However, the relevance of the Power of Attorney to Encumber Mortgage Rights needs to be reviewed, considering the length of the administration process at the National Land Agency.